Tumor-agnostic precision medicine from the AACR GENIE database: clinical implications - Gouda, Mohamed A.; Nelson, Blessie E.; Buschhorn, Lars; Wahida, Adam; Subbiah, Vivek (Clinical cancer research, 2023)
Biomarker-driven cancer therapy has revolutionized precision oncology. With a better understanding of tumor biology, tissue-agnostic targets have been characterized and explored, which ultimately led to therapeutics with pan-cancer efficacy. To date, five molecular biomarkers have obtained FDA tissue-agnostic approval for targeted therapies and immunotherapies. Those include BRAFV600E mutations, RET fusions, NTRK fusions, high tumor mutation burden (TMB), and deficient mismatch repair/high microsatellite instability (dMMR/MSI-High). Herein, we have used data from AACR project GENIE to explore the clinico-genomic landscape of these alterations. AACR GENIE is a publicly accessible registry of genomic data from multiple collaborating cancer centers. Current database (version 13.0) includes sequencing data of 168,423 samples collected from patients with different cancers. We were able to identify BRAFV600E, RET fusions, NTRK fusions, and high TMB in 2.9%, 1.6%, 1.5%, and 15.2% of pan-cancer samples, respectively. In this article, we describe the distribution of those tissue-agnostic targets among different cancer types. In addition, we summarize the current prospect on the biology of these alterations and evidence on approved drugs, including pembrolizumab, dostarilmab, larotrectinib, entrectinib, selpercatinib, and dabrafenib/trametinib combination.